2009
DOI: 10.1080/14015430903066937
|View full text |Cite
|
Sign up to set email alerts
|

Oral motor dysfunction in children with adenotonsillar hypertrophy—effects of surgery

Abstract: Full terms and conditions of use: http://www.informaworld.com/terms-and-conditions-of-access.pdf This article may be used for research, teaching and private study purposes. Any substantial or systematic reproduction, re-distribution, re-selling, loan or sub-licensing, systematic supply or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 23 publications
(18 reference statements)
2
43
2
3
Order By: Relevance
“…Recent studies have shown that tonsillotomy has the same beneficial long-term effect on other obstructive symptoms such as sleep apnoea and snoring as tonsillectomy, while causing lower primary morbidity and less pain (21,22). In a previous publication the present authors have shown that oral-motor function is equally improved after both tonsillectomy and tonsillotomy (23). The aim of the present study is to perceptually and acoustically evaluate vocal function in preschool children with hypertrophic adenotonsillar tissue in comparison to healthy children.…”
Section: Introduction/backgroundmentioning
confidence: 65%
See 1 more Smart Citation
“…Recent studies have shown that tonsillotomy has the same beneficial long-term effect on other obstructive symptoms such as sleep apnoea and snoring as tonsillectomy, while causing lower primary morbidity and less pain (21,22). In a previous publication the present authors have shown that oral-motor function is equally improved after both tonsillectomy and tonsillotomy (23). The aim of the present study is to perceptually and acoustically evaluate vocal function in preschool children with hypertrophic adenotonsillar tissue in comparison to healthy children.…”
Section: Introduction/backgroundmentioning
confidence: 65%
“…The frequency of the third formant has been shown to be influenced by the tip of the tongue (25) In a previous study, oral motor function was investigated in the same children as in the present (23) . A protruding positioning of the tip of the tongue was found more often in the children with tonsillar hypertrophy than in corresponding control group.…”
Section: Discussionmentioning
confidence: 99%
“…This difference is also reflected in the results of the perceptual analysis made by the experienced listeners who judged the /s/-sounds of the children in the study groups to be significantly less distinct than those of the controls. These results can be explained by the oral motor problems that children with tonsillar hypertrophy experience (Lundeborg, McAllister, Graf et al, 2009). The production of the /s/-sound, with its demands on precise placements of the articulators, especially the tongue seems to be vulnerable to the structural alteration of the oral cavity that hypertropic tonsils cause.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous investigation on the same material we found that oral motor function regarding non speech activities was hampered in children with tonsillar hypertrophy and normalized after surgery (Lundeborg, McAllister, Graf, Ericsson, and Hultcrantz, 2009). The study also revealed some minor sex differences with the boys having somewhat larger problems before surgery than girls.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative controls should be mandatory and training programs to ensure nasal respiration if nasal breathing is not resumed [25].…”
Section: Discussionmentioning
confidence: 99%